Why Islam Entices Increasing Human Procreation? A Vector Error Correction Model (VECM) Analysis on Population and Economic Growth: The Case of the Philippines - Najeeb Razul A. Sali (International Journal on Economics, Finance and Sustainable Development, 2022)
This study investigated the effect of increasing population on economic growth. It highlights the Qur'anic injunctions as well as prophetic traditions pointing to the benefits of population growth and supports them with empirical findings using the Philippines settings as a case in point, it made use of econometrics data analysis using Augmented Dickey-Fuller test, the Johansen Cointegration, Vector Error Correction Model (VECM), Granger causality to analyze the time series data of the Philippine population from 1978 to 2020 as well as the country's Gross Domestic Product (GDP) from the same time frame as a proxy for economic growth of the Philippines. The result shows that with F-statistic = 4.26 and a p-value of 0.01, being p < 0.05 alpha level, it means that the null hypothesis that population does not Granger Cause GDP is rejected. On the contrary, with F-statistic = 0.49 and a p-value of 0.68, it suggested that the null hypothesis that GDP does not Granger Cause population is accepted. This study concludes that increasing population is associated with an increase in the size of the economy. In contrast, an in the economy does not lead to population growth in the country.